Comparative Analysis of Backdoor Listing Regulations in Indonesia and Singapore: Implications for Investor Protection - Nabila Sagita; Satino Satino (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
The development of backdoor listing practices as an alternative to share listings has created new dynamics in capital market law, particularly regarding investor protection. In Indonesia, transactions that substantially resemble backdoor listings are not regulated by a special regime but are instead subject to general takeover and information disclosure provisions. In contrast, Singapore classifies similar transactions as reverse takeovers (RTOs) or very substantial acquisitions (VSAs), with approval and disclosure mechanisms equivalent to initial public offerings (IPOs). The research problem is to examine the differences in backdoor listing regulations and how these differences impact investor protection, particularly minority investors. This study aims to analyze the comparative regulations between Indonesia and Singapore and assess their legal implications for the effectiveness of investor protection. The method used is normative legal research with a comparative approach, aiming to compare backdoor listing regulations in Indonesia and Singapore. The results show that the Indonesian model is reactive and administrative, resulting in repressive investor protection. In contrast, Singapore's approach is preventative through pre-transaction approval and comprehensive disclosure, which strengthens ex ante protection. It concludes that strengthening the disclosure regime and preventive approval is necessary to enhance investor protection in backdoor listing practices in Indonesia.